Genes involved in the development of Parkinson - Diana Teixeira; Inês Lopes Cardoso (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2017)
Background: Parkinson's disease is the second most important neurodegenerative disorder, affecting 3% of individuals older than 80 years of age. Main clinical symptoms are resting tremor, postural instability, bradykinesia and rigidity, with a good response to levodopa therapy. Purpose of the study: The main goal of this work is to make a deep analysis on the genetic factors and kind of heritage involved in the development of Parkinson. Main findings: Over the last years, numerous studies allowed to confirm the unquestionable contribution of genetic factors to the complex pathogenesis of this disease. Highly penetrant mutations producing rare, monogenic forms of the disease have been identified in singular genes such as SNCA, Parkin, DJ-1, PINK1, LRRK2, and VPS35. Unique variants with incomplete penetrance in LRRK2 and GBA genes were identified as strong risk factors for Parkinson's disease in certain populations. Additionally, over 20 common variants with small effect sizes are now recognized to modulate the risk for Parkinson's disease. Investigating Mendelian forms of Parkinson disease has provided precious insight into the pathophysiology that underlies the more common idiopathic form of this disorder.